2013
DOI: 10.1111/tmi.12053
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a maternal mortality surveillance system in Morocco – challenges and opportunities

Abstract: Abstractobjective To describe the development of the maternal death surveillance system (MDSS) in Morocco and discuss the initial results.method The nationwide MDSS was implemented in 2009 with the involvement of health professionals and local authorities. It comprises (i) notification of all deaths of women of reproductive age (from 15 to 49 years); (ii) a preliminary survey to identify pregnancy-related deaths; (iii) a confidential enquiry into all pregnancy-related deaths. The information thus obtained desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…Anaemia was the most common indirect cause of SMO in this current analysis. This is in accordance with other reports from developing countries; however, cardiac disease was the leading indirect cause of MD from developed countries …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Anaemia was the most common indirect cause of SMO in this current analysis. This is in accordance with other reports from developing countries; however, cardiac disease was the leading indirect cause of MD from developed countries …”
Section: Discussionsupporting
confidence: 93%
“…A very recent report from India including 39 704 live births and 120 MDs showed that 27.5% of MDs were the result of indirect causes, with anaemia and jaundice being the two most common causes . The maternal death surveillance system (MDSS) in Morocco, including 313 reviewed records, found that 13.5% were classified as indirect cause, and that heart disease was the main indirect cause of death . A hospital‐based review of maternal mortality in Ghana of 30 269 live births and 322 MDs indicated that 22.4% were from indirect causes, and that infection and sickle cell disease accounted for 61.1% of indirect causes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal mortality surveillance studies such as confidential enquiry have showed that late maternal death is non-trivial in even low-resource settings34,59 and can account for up to 40% of maternal deaths in high-income settings 60. A contemporary linkage study in Mexico found that 18% of maternal deaths are missed when the definition is truncated at 42 days’ post partum 61.…”
Section: Discussionmentioning
confidence: 99%
“…This change had the effect of substantially increasing the size of our analytical dataset with respect to time and geography. Late maternal death data from the causes-of-death database were limited to those location years where at least 0·5% of all maternal deaths in raw vital registration data files were coded to late maternal deaths as this was the lowest proportion reported in any surveillance studies 34. Only 39 countries met these criteria with variable times in which they began coding late maternal deaths.…”
Section: Methodsmentioning
confidence: 99%